Did the Strong Dollar Increase Competition in U.S. Product Markets? - Knetter, Michael M. (The Review of Economics and Statistics, 1994)
Sunk cost models of new trade theory have demonstrated that large, unanticipated swings in currency values can have permanent effects on trade flows by altering market structure in imperfectly competitive markets. The author tests an implication of these models using panel data on export unit values from Germany and Japan to a number of foreign markets, including the United States. He finds weak evidence in support of the thesis that U.S. product markets became more competitive as a result of the large dollar appreciation of the 1980s, although the results vary by industry and comparison country. Copyright 1994 by MIT Press.